2002
DOI: 10.1046/j.1537-2995.2002.00138.x
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and structural changes in RBCs stored with different plasticizers: the role of hexanol

Abstract: The hexanol component of the BHTC plasticizer in a concentration of 144.6 microg per mL concentration suppresses hemolysis and vesiculation of RBCs during storage. The hexanol and DEHP that are slowly leached during storage have a greater effect in suppressing hemolysis and vesicle formation than when added extraneously to AS-1 in PO containers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 39 publications
0
20
0
1
Order By: Relevance
“…The DEHP is known to have a beneficial effect on RBCs that are stored for transfusion, reducing susceptibility to hemolysis [8,9,10,29] and minimizing the formation of both echinocytes [10] and microparticles [8,9,10,11]. Hemolysis, vesicle formation, and the shape changes associated with echinocyte formation are associated with the membrane; together with the known association of DEHP with the RBC membrane [3], this makes the DEHP-membrane interactions a specific target to study.…”
Section: Discussionmentioning
confidence: 99%
“…The DEHP is known to have a beneficial effect on RBCs that are stored for transfusion, reducing susceptibility to hemolysis [8,9,10,29] and minimizing the formation of both echinocytes [10] and microparticles [8,9,10,11]. Hemolysis, vesicle formation, and the shape changes associated with echinocyte formation are associated with the membrane; together with the known association of DEHP with the RBC membrane [3], this makes the DEHP-membrane interactions a specific target to study.…”
Section: Discussionmentioning
confidence: 99%
“…14 Although microvesicles are relatively abundant in stored blood, 17 where vesiculation is promoted by low pH, decreased adenosine triphosphate (ATP) levels, and the anticoagulant, they are infrequent in circulating blood 14 where vesiculation primarily occurs extravascularly in the spleen. 18 When we identified microvesicles by size and staining with antiglycophorin and anti-CD59 mAb and assessed microvesicle number in healthy nontransfused controls (n ϭ 5), we found a mean of only 6 microvesicles/L blood (data not shown).…”
Section: Transfused Rbcs Are Rich In Cd59-expressing Microvesicles Amentioning
confidence: 99%
“…None of these plasticizers are devoid of potential health hazards but DINCH shows the lowest reproductive and developmental toxicity [6], which is also a DEHP-associated risk of concern for pediatric recipients. It has been previously shown that RBCs can be stored satisfactorily in BTHC-plasticized bags [12], despite inferior protection against hemolysis and vesiculation (assessed as the cell-free, membrane-bound protein concentration during storage) compared to DEHP [13]. DINCH has recently been reported to approach DEHP in terms of protection against hemolysis [14] with the advantage that it leaches less readily from the PVC matrix [15,16].…”
Section: Introductionmentioning
confidence: 99%